Neuroprotective Effect of β-Caryophyllene on Cerebral Ischemia-Reperfusion Injury via Regulation of Necroptotic Neuronal Death and Inflammation: In Vivo and in Vitro - Yang, Mei; Lv, Yongjiu; Tian, Xiaocui; Lou, Jie; An, Ruidi; Zhang, Qian; Li, Minghang; Xu, Lu; Dong, Zhi (Frontiers in Neuroscience, 2017)
Necrotic cell death is a hallmark feature of ischemic stroke and it may facilitate inflammation by releasing intracellular components after cell-membrane rupture. Previous studies reported that β-caryophyllene (BCP) mitigates cerebral ischemia-reperfusion (I/R) injury, but the underlying mechanism remains unclear. We explored whether BCP exerts a neuroprotective effect in cerebral I/R injury through inhibiting necroptotic cell death and inflammation. Primary neurons with and without BCP (0.2, 1, 5, 25 μM) treatment were exposed to oxygen-glucose deprivation and re-oxygenation (OGD/R). Neuron damage, neuronal death type and mixed lineage kinase domain-like (MLKL) protein expression were assessed 48 h after OGD/R. Furthermore, mice underwent I/R procedures with or without BCP (8, 24, 72 mg/kg, ip.). Neurologic dysfunction, cerebral infarct volumes, cell death, cytokine levels, necroptosis core molecules, and HMGB1-TLR4 signaling were determined at 48 h after I/R. BCP (5 μM) significantly reduced necroptotic neurons and MLKL protein expression following OGD/R. BCP (24, 72 mg/kg, ip.) reduced infarct volumes, neuronal necrosis, receptor-interaction protein kinase-1 (RIPK1), receptor-interaction protein kinase-3 (RIPK3) expression and MLKL phosphorylation after I/R injury. BCP also decreased high-mobility group box 1 (HMGB1), toll-like receptor 4 (TLR4), interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) levels. Thus, BCP alleviates ischemic brain damage potentially by inhibiting necroptotic neuronal death and inflammatory response. This study suggests a novel application for BCP as a neuroprotective agent.